Employer Attitudes and the Hiring of Immigrants and International Students: Evidence from a Survey of Employers in Canada - Tony Fang; Na Xiao; Jane Zhu; John Hartley (Institute of Labor Economics (IZA), 2022)
What are the perceptions of employers towards hiring immigrants and international students in Atlantic Canada? How are they related to hiring outcomes? Our analysis based on a 2019 random, representative survey of 801 employers finds that those employers who report beliefs that multiculturalism is creativity-enhancing in the workplace and that immigrants are harder working than local workers are more likely to report hiring or intending to hire newcomers and international students Although most employers report positive attitudes towards newcomers and international students, employers who report perceptions that immigrants tend to take jobs from domestic workers, accept lower pay, have a lower retention probability, face language barriers, have higher training costs, and hold unreliable credentials are less likely to report hiring from this group.
Keywords: J23; J61; J63; J68; 330; immigrants; international students; labour and skill shortages; employer hiring attitudes; employer survey; Atlantic Canada